A fórmula discursiva “globalização” nos cadernos do professor de geografia do Estado de São Paulo - Guiraldelli, Talita de Carvalho (2017)
One of the ways to present the discourses and the way in which the debates about how social relations aim at the study of discursive formulas and their variants, as proposed by Krieg-Planque (2010). Such formulas are verbal, formally demarcable, and relatively stable sequences that begin to function in discourses produced in the public space as expressions that are both shared and polemical. A discursive formula is characterized by the fact that it is a social referent, that is, at a given moment, it circulates in different sectors (educational, religious, political, journalistic, etc.) in different discursive genres (manuals, news, reports, etc.) And on different media (newspapers, websites, etc.). In this research, the objective is to study the way in which the globalization formula and its possible variants circulate in the six volumes of the Teacher's Book of Geography of Secondary Education of the Secretary of Education of the Government of the State of São Paulo. It seeks to reflect on the circulation of the formula and how it mobilizes the teacher's performance and the student's thinking about this constantly evolving process in the contemporary scenario. For this, a bibliographical research was used and, from the reading of the notebooks, it was tried to understand the effects of sense constructed by the discursive formula Globalization, in relation to the teacher and the student before the learning process, based on the theoretical methodological analysis of the Discourse Analysis of French line (AD) and the main concept mobilized will be that of discursive formula. Key-words: discursive formulas; globalization; geography; teacher's notebooks.